Analisis Hubungan Getaran dan Kualitas Kebulatan Pada Proses Pembubutan Baja ST60 - Anselmus Agung Wilko Yonico; Robert Napitupulu; Nanda Pranandita (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
This study aims to analyze the relationship between machine vibration and roundness quality in the turning process of ST 60 steel. An experimental method was conducted by varying three main cutting parameters: depth of cut (2 mm and 3 mm), spindle speed (700 RPM and 995 RPM), and feed rate (0.7 mm/rev and 1 mm/rev). Vibration was measured using a vibrameter (VibraPort 80), while roundness quality/surface roughness (Ra) was measured using a micrometer and a surface roughness tester. The results indicated that the increase in vibration intensity is directly proportional to the increase in surface roughness/roundness values, with vibration acting as a mediator that degrades the quality of the turning results. Feed rate was identified as the most dominant parameter affecting both vibration and roundness quality. Increasing the feed rate from 0.7 to 1 mm/rev expanded the tool path markers, resulting in a coarser surface. Conversely, higher spindle speeds tended to produce a more stable cutting process and dampen vibrations, although extreme RPMs could trigger chatter. The conclusion shows that vibration control through parameter optimization, particularly the use of low feed rates and stable high RPMs, is crucial for achieving precision in ST 60 steel turning with an optimal Ra value below 1.5 μm.